The Effect of S-Commerce Tiktok Shop Recommendation Products on Changes in Consumer Impulsive Buying Behavior: A Study with Signaling Theory - Asharinnisa Salsabila; Budi Prasetyo (Journal of Advances in Information Systems and Technology, 2024)
Product recommendation was introduced as a marketing technique that is quite commonly used in online shopping platforms, one of which is TikTok Shop. The use of recommended products in the digital market environment is intended to learn consumer interests and preferences so that the target market can conduct marketing. It is expected to make it easier for consumers to find their desired products. However, the use of product recommendations in the digital market also has the potential to have a negative effect in the form of forming consumer impulsive behavior. For this reason, this research was conducted to understand what factors of product recommendations can motivate consumer impulsive behavior at TikTok Shop and to see the effectiveness of video advertisements in motivating consumers to make purchases. In its implementation, this research uses the principles of signaling theory as the basis of research. Then, the research was carried out using a quantitative approach to collect and process data. The data collection method was carried out through questionnaire distribution by utilizing Google form as a data collection medium and social media as a medium for distributing questionnaires. Meanwhile, the data from the questionnaire was processed using the SmartPLS 3 application. The study results show that providing product recommendations through video content (VC) has the potential to shape consumer impulsive behavior.